Fuzzy-PI Control for Buck Converter Output Voltage Stabilizer - Ihsan Al-Fikri; Aripriharta Ph.D; Anik Nur Handayani; Norzanah Rosmin; Saodah Omar (Faculty of Engineering, Universitas Tanjungpura, 2022)
This paper presents a hybrid control between Fuzzy and PI to solve the problem of stability of the output voltage on the Buck Converter, especially in small power applications. This paper makes two main contributions. The first is the design of a simple Fuzzy-PI output voltage control design of a buck converter in Matlab. The second is the result of comparing the response of the traditional PI control system with the designed Fuzzy-PI hybrid control. The method used is a simulation with 3 stages. This process starts from the design of the Fuzzy-PI controller, simulation test with 3 scenarios, and verification with a comparison, namely the PI controller. The purpose of the simulation is to see the response of the system to changes in input voltage, reference voltage, and load resistance. Based on the test results, it is known that the Fuzzy-PI control is better than the PI control in maintaining the stability of the buck converter output voltage at every parameter change.